3x+4=-3x+28

Simple and best practice solution for 3x+4=-3x+28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+4=-3x+28 equation:


Simplifying
3x + 4 = -3x + 28

Reorder the terms:
4 + 3x = -3x + 28

Reorder the terms:
4 + 3x = 28 + -3x

Solving
4 + 3x = 28 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
4 + 3x + 3x = 28 + -3x + 3x

Combine like terms: 3x + 3x = 6x
4 + 6x = 28 + -3x + 3x

Combine like terms: -3x + 3x = 0
4 + 6x = 28 + 0
4 + 6x = 28

Add '-4' to each side of the equation.
4 + -4 + 6x = 28 + -4

Combine like terms: 4 + -4 = 0
0 + 6x = 28 + -4
6x = 28 + -4

Combine like terms: 28 + -4 = 24
6x = 24

Divide each side by '6'.
x = 4

Simplifying
x = 4

See similar equations:

| (2a^4b-3a^4+6b)+(5a^4-9a^4-8b)= | | -2x+1=2x-19 | | 8(x-7)=6(x-4) | | 3x^2-5+1=0 | | 2x+108=8x+60 | | 3x+12y=-30 | | -7x+5(8+9n)=4(9n+1) | | -(7x+3)-(5x-3)=7-(2x+1) | | 2Y=3X-Y | | 3(-2)-1=-2-5 | | 3x+41=65 | | 12(-2b-12)=-6(-3b+10) | | -2x+1=3x-9 | | -5x=-2x-6 | | 7500x=5900x+88000 | | (x+72)(x+48)=6912 | | -15-32n=4(-8n+4) | | 120-5a+7=8a-16a-35 | | 8y+1=9y-7 | | 4x+89=7x-74 | | 3x+2=3x-3 | | 4h^2=-62h-30 | | 2x/3=15 | | 2x/3-9=32 | | (7x^2-3x-16)+(8x^2+8x)= | | 240x+35=5y+135x | | 3x^3=81 | | 6y=z | | 3(3e+2f)+yf+2=0 | | Y=5/2x+1 | | 4x+3x+5= | | 24+b=40 |

Equations solver categories